2022
DOI: 10.3174/ajnr.a7644
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Characteristics of CNS Neuroblastoma-FOXR2: A Retrospective and Multi-Institutional Description of 25 Cases

Abstract: BACKGROUND AND PURPOSE: The 5th edition of the World Health Organization Classification of CNS tumors defines the CNS neuroblastoma FOXR2 in the group of embryonal tumors. Published clinical outcomes tend to suggest a favorable outcome after resection, craniospinal irradiation, and chemotherapy. This multicenter study aimed to describe imaging features of CNS neuroblastoma-FOXR2, which have been poorly characterized thus far. MATERIALS AND METHODS:On the basis of a previously published cohort of tumors molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 23 publications
1
12
0
Order By: Relevance
“…Tietze et al. reported that supratentorial location, often large size, multilobulated tumor shape, little‐or‐no perifocal edema, presence of nonsolid components, 22 T2WI hyperintensity compared to the cortex, low ADC values, and susceptibility artifact on T2‐ or susceptibility‐weighted images were frequently found, and these imaging features were also verified in this systematic review. We also identified that on nonenhanced CT, solid components of CNS NB‐FOXR2 appeared hyperdense (4/5, 80%) or isodense (1/5, 20%) relative to the cortex with characteristic calcification along the inner rim (4/5, 80%).…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Tietze et al. reported that supratentorial location, often large size, multilobulated tumor shape, little‐or‐no perifocal edema, presence of nonsolid components, 22 T2WI hyperintensity compared to the cortex, low ADC values, and susceptibility artifact on T2‐ or susceptibility‐weighted images were frequently found, and these imaging features were also verified in this systematic review. We also identified that on nonenhanced CT, solid components of CNS NB‐FOXR2 appeared hyperdense (4/5, 80%) or isodense (1/5, 20%) relative to the cortex with characteristic calcification along the inner rim (4/5, 80%).…”
Section: Discussionsupporting
confidence: 76%
“…We screened these results according to the PRISMA 2020 guideline and narrowed them down to potentially eligible studies by removing duplicates, and irrelevant studies by title and abstract screening. After excluding 33 studies based on the exclusion criteria, six studies with 31 patients with CNS NB‐FOXR2 satisfied the criteria for the systematic review 3,18–22 . Other than 25 case series by Tietze et al., 22 which focused on MR imaging features, these studies were case‐based reports 3,18–21 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…67 The median age is 4.5 years (range, 1.4-16 years) without a sex predilection. 69 In the largest described series, tumors were large and supratentorial with invariable involvement of the deep white matter and frequent invasion of the cortex (80%) as well as a ventricular ependymal surface (64%). 69 The frontal lobe was the most common location, though involvement of multiple regions was common.…”
Section: Cns Neuroblastoma Foxr2-activatedmentioning
confidence: 95%
“…69 In the largest described series, tumors were large and supratentorial with invariable involvement of the deep white matter and frequent invasion of the cortex (80%) as well as a ventricular ependymal surface (64%). 69 The frontal lobe was the most common location, though involvement of multiple regions was common. Typical tumors were multilobulated, solid, and cystic/necrotic, T2-hyperintense, enhancing, and diffusion-restricting ( Fig 10).…”
Section: Cns Neuroblastoma Foxr2-activatedmentioning
confidence: 95%